Knowledge, attitude, and practice of nurses towards frailty syndrome: a multicenter cross-sectional survey in Fujian Province, China - Chen, Hong; Chen, Maohe; Luan, Ruina; Chen, Chunying; Su, Meiyun; Hong, Pingping; Guo, Jun; Zhu, Bifang; Lin, Hanbin; Lin, Ping (Frontiers in Medicine, 2026)
BackgroundFrailty is a global geriatric challenge requiring integrated nursing management. However, the mechanism driving nurses’ practice behaviors remains unclear. This study aimed to evaluate the status of knowledge, attitude, and practice (KAP) regarding frailty syndrome among nurses and identify the independent predictors of clinical practiceMethodsA multicenter cross-sectional survey was conducted among 598 registered nurses in Fujian, China, using a structured questionnaire. Data were analyzed using descriptive statistics and multiple linear regression to identify predictors of practice scores while adjusting for potential confoundersResultsParticipants demonstrated foundational theoretical knowledge of frailty definitions but exhibited substantial gaps in practical application, particularly in identifying risk factors and conducting comprehensive assessments. While univariate analysis suggested associations between practice scores and factors like knowledge, age, and education, the multivariate model revealed that Attitude was the sole robust independent predictor (β = 0.67, p < 0.001). Notably, knowledge and demographic variables lost statistical significance after adjustment (p > 0.05), indicating a distinct “knowledge-practice gap” where theoretical competence does not automatically translate into clinical action without intrinsic motivationConclusionA significant dissociation exists between nurses’ theoretical knowledge and their actual practice behaviors in frailty care. Since attitude acts as the decisive mediator overriding demographic barriers, future clinical pathways should shift from purely didactic training to fostering a proactive professional culture. Interventions must prioritize motivational strategies to bridge the knowledge-practice gap and optimize patient safety outcomes.